2020
DOI: 10.1142/s021759082049003x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ict on Service Trade

Abstract: While trade in goods has been investigated extensively over decades, studies on trade in services are relatively new. In this paper, we investigate the impacts of information and communication technology (ICT) on trade in services. We measured ICT by four dimensions, including the subscriptions to broadband, fixed telephones, mobile phones and Internet. Our sample covered more than 200 countries from 2005 to 2015. We employed the modified gravity model and found that all four dimensions had significant impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…However, the variables of foreign direct investment, real exchange rate, communication facilities, real exchange rate, and gross domestic product were found to have a significant impact on trade in services exports. [13] measured the influence of ICT on the services trade of world countries and found that the dimensions of ICT with the variables of broadband subscriptions, internet users, fixed telephone subscriptions and cellular telephones had a positive effect on the value of services trade. An increase in population and gross domestic product will increase the value of trade in services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the variables of foreign direct investment, real exchange rate, communication facilities, real exchange rate, and gross domestic product were found to have a significant impact on trade in services exports. [13] measured the influence of ICT on the services trade of world countries and found that the dimensions of ICT with the variables of broadband subscriptions, internet users, fixed telephone subscriptions and cellular telephones had a positive effect on the value of services trade. An increase in population and gross domestic product will increase the value of trade in services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[10] use GDP per capita and find that GDP per capita affects service exports positively. Real gross domestic product is also widely used in research and it is found that GDP has a positive influence on service exports [8][11] [13]. The GDP used in this study is a constant GDP with a base year 2010 (real GDP) in billions US dollars.…”
Section: Gross Domestic Productmentioning
confidence: 99%
See 3 more Smart Citations